Pengaruh Promosi Word of Mouth, Harga dan Kualitas Pelayanan terhadap Kepuasan Konsumen Apotek Tegalglagah Sehat - Priska Amelia; Hendri Sucipto; Muhammad Syaifulloh; Dumadi Dumadi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to determine the influence of word of mouth promotion, price, and service quality on consumer satisfaction at Tegalglagah Sehat Pharmacy. The research method used is a quantitative approach with a descriptive and verifiable design. The research sample amounted to 88 respondents who were determined using the Slovin formula, and data collection was carried out through questionnaires. The data analysis technique uses the Partial Least Square (PLS) approach with the help of SmartPLS 4.0 software. The results of the study show that the three independent variables, namely word of mouth promotion, price, and service quality, have a positive and significant influence on consumer satisfaction, both partially and simultaneously. These findings reinforce the importance of the role of these three variables in shaping consumer perception and experience of services in pharmacies. Among the three, service quality has proven to be the most dominant variable affecting consumer satisfaction. This reflects that the better the quality of service provided by the pharmacy, the higher the level of satisfaction felt by consumers. Thus, improving the quality of service is a strategic priority that cannot be ignored by pharmacy management. In addition, maintaining competitive price stability and strengthening promotions through word of mouth is also an important step in maintaining and increasing customer loyalty. This strategy is not only important for retaining existing consumers, but also for attracting new consumers through positive recommendations that develop through word of mouth. Furthermore, the results of this study also indicate that pharmacy consumers are increasingly selective and critical in evaluating the health services they receive.